Peer Assessment Training on EFL Writing for Lower Proficiency Level, Is It Worthy? - herlinawati herlinawati (Universitas Lancang Kuning, 2019)
The present study was conducted to investigate whether training on peer assessment could foster better writing ability for English lower proficiency EFL students. Forty-eight (48) students participated in this study and randomly assigned into two groups; trained and untrained peer assessment. Trained group is as experimental group and untrained group is as control group. The students’ English proficiency level was lower to higher based on the results of TOEFL test scores. A pre-writing test of argumentative essay was given before providing the training. Then, the students in experimental group was given peer assessment training before instructing them to rate their peers drafts. The whole sessions were lasted in six sessions. The pre-test was administered before giving the six sessions to apply the treatment; and a post test was given at the end of the session to determine the effects of peer assessment training on students’ writing ability. The result of analysis revealed significant between-group differences, F (2, 816) = 3.440, p (.020) < .05. the lower proficiency in trained group performed better than the higher and lower proficiency students in untrained group.